The AI-knowledge management nexus for sustainable learning: A PLS-SEM study - Sashi Ranjan; V. P. Joshith; K. Kavitha; Shana Chittakath (Knowledge Management & E-Learning: An International Journal)
Integrating artificial intelligence (AI) with knowledge management (KM) practices presents a promising avenue for advancing sustainable learning in higher education. However, empirical research exploring this synergy remains limited, particularly in developing countries. This study aimed to investigate the impact of AI-enhanced KM practices on sustainable learning outcomes in Indian higher education institutions. A proposed model was tested using a sample of 401 student responses, analysed through partial least square equation modelling (PLS-SEM) using SmartPLS 4. The findings revealed that AI-driven knowledge creation, storage, discovery, and prediction significantly contribute to sustainable learning when implemented ethically. Conversely, AI-based knowledge capture practices and tailored knowledge delivery did not significantly influence sustainable learning environments. The model exhibited substantial explanatory power regarding sustainable learning outcomes. This study contributes to the “knowledge-based view” and “absorptive capacity” theory by exploring the integration of AI and KM in education. Furthermore, it advances the “responsible AI paradigm” by addressing ethical considerations in AI-enhanced educational systems. The results provide a foundation for future research on the interplay between AI, KM, and sustainable learning, offering valuable insights for transforming educational practices and promoting lifelong learning in higher education.